Extensible lateral approach versus sinus tarsi approach for sanders type II and III calcaneal fractures osteosynthesis: a randomized controlled trial of 186 fractures - Amr A. Fadle; Ahmed A. Khalifa; Peter Mamdouh Shehata; Wael EL-Adly; Ahmed Ekram Osman (Journal of Orthopaedic Surgery and Research)
Abstract Aims Which is the best extensile lateral (ELA) or sinus tarsi (STA) approach for osteosynthesis displaced intraarticular calcaneal fracture (DIACF) is still debatable. The current RCT’s primary objective was to compare the complications incidence after open reduction and internal fixation of DIACFs through STA vs. ELA. The secondary objectives were the differences in intraoperative radiation exposure, time to fracture union, functional and radiological outcomes. Methods Between August 2020 and February 2023, 157 patients with Sanders type II and III fractures were randomly assigned to either ELA (81 patients with 95 fractures) or STA (76 patients with 91 fractures). The primary outcome was the incidence of complications. The secondary outcomes were Böhler’s and Gissane angles angle, fracture union, and American Orthopaedic Foot and Ankle Society (AOFAS) score. Results No statistical differences between both groups regarding basic demographic data, injury characteristics, and fracture classification; however, patients in the STA group were operated upon significantly earlier (4.43 ± 7.37 vs. 7 ± 6.42 days, p = 0.001). STA’s operative time was significantly shorter (55.83 ± 7.35 vs. 89.66 ± 7.12 min, p < 0.05), and no statistical difference regarding intraoperative radiation exposure. The time to fracture union was significantly shorter in STA (6.33 ± 0.8 vs. 7.13 ± 0.7 weeks, p = 0.000). Skin complications (superficial or deep infection) and Subtalar osteoarthritis were significantly higher in ELA (18.9% vs. 3.3%, p = 0.001) and (32.6% vs. 9.9%, p = 0.001), respectively. The radiological parameters were significantly better in STA postoperatively and at the last follow up. The AOFAS scores were significantly better in STA (83.49 ± 7.71 vs. 68.62 ± 7.05, respectively, p = 0.000). Conclusion During osteosynthesis of Sanders type II and III DIACFs, STA is superior to ELA in terms of operating earlier, shorter operative time, fewer complications, and better radiological and functional outcomes.